Online social networks and trust - Fabio Sabatini; Francesco Sarracino (Economics and Econometrics Research Institute (EERI), 2015)
We explore how participation in social networking sites (SNS) such as Facebook and Twitter affects the most economically relevant aspect of social capital, trust. We use measures of trust in strangers (or social trust), trust in neighbours and trust in the police. We address endogeneity in the use of SNS by exploiting the variation in the availability of broadband for high-speed Internet, which relates to technological characteristics of the pre- existing voice telecommunication infrastructures. We find that all the proxies of trust significantly decrease with participation in online networks. We discuss several interpretations of the results in light of the specific features of Internet-mediated social interaction.
Keywords: C36; D85; O33; Z1; 330; Internet; broadband; online networks; social networking sites; Facebook; trust; social capital; hate speech